2013
DOI: 10.1128/ec.00169-13
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Source-Dependent Capsule Induction in Human-Pathogenic Cryptococcus Species

Abstract: Cryptococcus neoformans and C. gattii cause meningoencephalitis and are an increasing human health threat. These pathogenic Cryptococcus species are neurotropic and persist in the cerebrospinal fluid (CSF) of the mammalian host during infection. In order to survive in the host, pathogenic fungi must procure nutrients, such as carbon and nitrogen, from the CSF. To enhance our understanding of nutrient acquisition during central nervous system infection by Cryptococcus species, we examined the utilization of nit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…Similarly, the extracellular ureases of C. neoformans and Cryptococcus gattii (Ure1) degrade urea, which is abundant in the cerebrospinal fluid. The liberated CO 2 acts as a signal to induce capsule formation, a well-studied virulence factor in this fungus (Frazzitta et al 2013).…”
Section: Nitrogen Acquisition In Host Nichesmentioning
confidence: 99%
“…Similarly, the extracellular ureases of C. neoformans and Cryptococcus gattii (Ure1) degrade urea, which is abundant in the cerebrospinal fluid. The liberated CO 2 acts as a signal to induce capsule formation, a well-studied virulence factor in this fungus (Frazzitta et al 2013).…”
Section: Nitrogen Acquisition In Host Nichesmentioning
confidence: 99%
“…How this link is achieved in these fungi remains be elucidated. In C. neoformans , there is evidence that higher expression of an amino acid permease is correlated with the phenotypes regulated by PKA; treatment with urea results in a 27-fold increase of an amino acid permease (CNAG_01118) and increased capsule production that is known to be regulated by PKA (6668). Our current study investigates the links between calcineurin, amino acid permease, and PKA which could also exist in C. neoformans and possibly other fungi.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there was a positive relationship between green area and the number of both CRF and non‐CRF fungi that can colonize pigeon faeces. These two factors, in combination with evidence that some CRF are better adapted to pigeon faeces than non‐CRF (Litvintseva et al., ; Mantovani, ), may selectively increase the relative abundance of CRF species (Frazzita et al., ; Lee et al., , ; Xue, ). Finally, the density of CRF may decrease with increasing wind speeds, because high wind speed can decrease the level of airborne fungi and thus decrease the number of spores settling on faeces (Guinea et al., ; Hasnain, ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies, however, suggest a more serious health threat appears to be their excrement, which is ubiquitous in urban areas. The chemical composition of pigeon faeces, specifically the availability of nitrogen from uric acid, creates an excellent substrate for fungal spores to propagate, and several studies have shown that pathogenic fungi metabolize faecal compounds during various developmental processes (Frazzita et al., ; Lee, Chow, Morrow, Djordjevic, & Fraser, ; Lee et al., ; Xue, ).…”
Section: Introductionmentioning
confidence: 99%